2006
DOI: 10.1108/03074350710688297
|View full text |Cite
|
Sign up to set email alerts
|

Finance: on earth as it is in heaven?

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The results of the study on the application of Christian values in Decision Making financing at STTPA are in line with the results of the Steen, et al (2006), namely the Financial decision on Operational Financing at STTPA has the main objective to bring peace to all parties at the institution. Peace is realized by establishing decisions that show concern for students and all parties in the STTPA ranks.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The results of the study on the application of Christian values in Decision Making financing at STTPA are in line with the results of the Steen, et al (2006), namely the Financial decision on Operational Financing at STTPA has the main objective to bring peace to all parties at the institution. Peace is realized by establishing decisions that show concern for students and all parties in the STTPA ranks.…”
Section: Resultssupporting
confidence: 77%
“…Christian values that influence Christian behavior are love (Matthew, 22: 37-39), prayer and work (2 Thessalonians, 3: 6-14), stewardship (Ephesians, 2:10), and social balance (Galatians, 6: 2). Research conducted by Steen, et al (2006), revealed that Christian values need to be included in the Decision Making process so that managers make financial decisions that can glorify God and create peace, where financing decisions are one form of financial decision formulated by managers. Furthermore, research conducted by Yaghi (2008),emphasizes that religious values influence the Decision Making process and organizational culture, where decisions taken by the leadership of the organization have the religious meaning contained in it.…”
mentioning
confidence: 99%
“…Burkett (1990) explained that making money should follow the main guidance principles given by God. As said Steen et al (2006), finance is an integral part of God's intended structure for the whole world. Finance must contribute to the universal flourishing of humankind and all other species on Earth.…”
Section: Christianity and Ethical Investingmentioning
confidence: 99%